Assessing Tenth-Graders’ Writing Skills and Identifying Their Character-Based Learning Contribution through a Mind Map Learning Model - Sukmayati, Mesya; Sumekto, Didik Rinan; Ratna Widayanti, Sukasih (LPPM Universitas Pancasakti Tegal, 2020)
This study aims at assessing tenth-graders’ writing skills and identifying their character-based learning contribution in the writing class. This study involved thirty-six tenth-graders to be the respondents who engaged in applying for the mind maps learning model. Data collection used tenth-graders’ narrative writing test and self-rated questionnaire through a 5-Likert scoring rubric accordingly. Data analysis used the SPSS program in order to obtain the expected quantitative analyses. The findings showed that tenth-graders’ writing skills improved from the pre-test (M = 66.25) to the post-test (M = 70.77), whilst tenth-graders’ narrative writing components significantly showed that vocabulary, grammar, cohesion and coherence, mechanics, and content. The findings also emphasized the character-based learning contribution followingly on the value of honesty, cooperation, communication, and respectfulness among the tenth-graders. Meanwhile, the factorability significance of the correlational matrix corresponded with the output of the principal component analysis (PCA) inferring the existence of five factors involving the Eigenvalue. This study was granted to be successful in assessing tenth-graders’ writing skills and identifying their character-based learning contribution through the mind maps learning model.